Shop drawing of aluminum sun shade (CW01-05) (RFA-022_Rev.A) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.